The world according to Roger Ballen - Rhodes, Colin 19XX- (Thames & Hudson, 2019)
'The World According to Roger Ballen', co-authored with Colin Rhodes, looks at Ballen's career in the wider cultural context beyond photography, including his connections with and collections of Art Brut. It features photographs selected from across Ballen's career, along with installations created exclusively for the exhibition at Halle Saint Pierre and photographs of objects and works from Ballen's own collection of Art Brut. Organized thematically, with texts by Colin Rhodes and an introduction and interview with Ballen by Martine Lusardy (the Director of the Halle Saint Pierre), The World According to Roger Ballen is both a catalogue of the first, major exhibition of Ballen's work in France and an exploration of Ballen's positioning within and connections to the wider context of modern and contemporary art
"Published on the occasion of the exhibition 'The world according to Roger Ballen' at the Musée de la Halle Saint Pierre, Paris, 7 September 2019 - 31 July 2020."--Colophon
Keywords: Ballen, Roger -- 1950-; Ballen, Roger / 1950-; Photography, Artistic; Art brut; Ausstellungskatalog -- Musée d'Art Naïf Max Fourny -- 07.09.2019-31.07.2020 -- Paris; Bildband